Świat rzeczy przedstawiciela inteligencji warszawskiej w okresie międzypowstaniowym – przykład Juliana Bartoszewicza - Florczak, Ilona (W zwierciadle rzeczy, 2022)
Julian Bartoszewicz’s world of things did not differ from similar worlds of other representatives of the Warsaw intelligentsia at that time, especially in terms of home furnishing and wardrobe. An average amount of furniture, a modest wardrobe and a limited number of everyday items – the furnishings of the apartment did not differ either in quality or quantity from the standard in second half of 19th century. The only exception, which should be emphasized, was the large library, the content of which clearly defined the interests and passions of its owner. The collection created by Bartoszewicz, which was a specific workshop of his work, was also much more valuable than the estimate expressed in rubles indicated. Its value also clearly indicated the historian’s attitude to material things, for whom manuscripts and old books were the most important.